1982
DOI: 10.1177/0310057x8201000107
|View full text |Cite
|
Sign up to set email alerts
|

Midazolam as an Intravenous Induction Agent for General Anaesthesia: A Clinical Trial

Abstract: The peripheral and central nervous, cardiovascular and respiratory effects of midazolam 0.15 mglkg, administered intravenously, were studied in 57 patients. Midazolam induced anaesthesia satisfactorily in 78% of the patients, the remainder required either further doses of midazolam, or alternative induction agents. There was no pain on injection. No evidence of thrombophlebitis was apparent up to 72 hours after injection. Mean systolic arterial pressure decreased from 128 mm Hg to 114 mm Hg and mean diastolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Patients showed a decrease in mean respiratory rate from 13.7 breaths/min to 12.8 breaths/ min two minutes after injection of midazolam. 20 When midazolam is administered intravenously for induction of general anaesthesia, respiratory depression occurs through a marked decrease in the ventilatory response to carbon dioxide. 21 Our study showed the lower post-operative incidence of nausea and vomiting was observed in midazolam compared to thiopentone with incidence thrombophlebitis was found more in thiopentone groups Study conducted by Abraham, J et al 15 , found postoperative nausea, vomiting and thrombophlebitis were significantly low with midazolam.…”
Section: Discussionmentioning
confidence: 99%
“…Patients showed a decrease in mean respiratory rate from 13.7 breaths/min to 12.8 breaths/ min two minutes after injection of midazolam. 20 When midazolam is administered intravenously for induction of general anaesthesia, respiratory depression occurs through a marked decrease in the ventilatory response to carbon dioxide. 21 Our study showed the lower post-operative incidence of nausea and vomiting was observed in midazolam compared to thiopentone with incidence thrombophlebitis was found more in thiopentone groups Study conducted by Abraham, J et al 15 , found postoperative nausea, vomiting and thrombophlebitis were significantly low with midazolam.…”
Section: Discussionmentioning
confidence: 99%
“…2 -5 Recently, midazolam, a watersoluble imidazo-benzodiazepine with a relatively short half-life, 6 has been introduced in clinical anaesthesia practice. With midazolam's short half-life, the length of postoperative somnolence is reduced 7 and its water solubility attenuates venous irritation at the injection site 8 and produces a relatively rapid induction time. 9 The purpose of our study was to compare the ·M.D., Associate Professor.…”
mentioning
confidence: 99%